“Per si muove—it was a mass of moonstone”: Fluidity, Dynamic Relations, and the Commodification of Storytelling in Harriet Prescott Spofford’s Arctic Writings - Verena Laschinger (European Journal of American Studies)
The essay examines Harriet Prescott Spofford’s short story “The Moonstone Mass” (1868) through the lens of fluidity foregrounded by her Arctic poem “The Story of the Iceberg” (1897). Rendering a network of actors (human and other), who are connected and continuously influence one another, “The Moonstone Mass” demands an analysis that acknowledges relationality as facilitating the protagonist’s discovery of the Northwest Passage alongside other metaphorical pathways, which the geographical trope symbolizes in the text. I argue that “The Moonstone Mass” fictionally renders an (imaginary) geographical journey to describe the complexities and challenges of personal, generational and societal transfers from the culturally conspicuous perspective of the nineteenth-century American storyteller transitioning from the era of Romanticism to Realism.